Online Physician Reviews in Female Pelvic Medicine and Reconstructive Surgery: What Do Patients Really Want?. Issue 2 (March 2018) - Asanad, Kian; Parameshwar, Pooja S.; Houman, Justin; Spiegel, Brennan M.; Daskivich, Timothy J.; Anger, Jennifer T.
Abstract : Objectives: This study aimed to qualitatively analyze online reviews of Female Pelvic Medicine and Reconstructive Surgery (FPMRS) specialists to better understand patients' experiences and improve patient satisfaction. Methods: Fifty urologists and urogynecologists were randomly sampled from the Society of Urodynamics, Female Pelvic Medicine, and Urogenital Reconstruction membership website. We evaluated patient ratings and reviews of physicians from 4 websites: Yelp, Healthgrades, Vitals, and UCompareHealthCare. Qualitative data analysis was performed using grounded theory methodology, as described by Charmaz ( Constructing Grounded Theory, 2014). Results: Across the four websites, the mean number of stars per physician ranged from 3.6 to 4.1 and the mean number of reviews per physician ranged from 1.3 to 7.6. Qualitative analysis revealed several preliminary themes: patient–physician experience, medical and surgical treatment, office staff, and analysis of worth. Physicians who developed strong connections with patients through empathetic communication were likely to receive a positive review, regardless of wait times. Bedside manner was found to be multidimensional and included physician competence and understanding patients' concerns. Failure to meet several expectations led to dissatisfaction of care and negative patient reviews. Conclusions: Patients' perspectives of quality of care in FPMRS are weighted heavily toward establishing personal connections with physicians. Accurate diagnosis and effective management of urological conditions, especially after negative experiences with previous providers, were associated with satisfaction of care. It seems that the concept of good bedside manner is multifactorial and requires the provider to demonstrate not one but several different sets of communication skills. Abstract : Qualitative analysis of 4 physician-rating Web sites offers insight into the patient experience and gives us the impetus to encourage female pelvic medicine and reconstructive surgery specialists to improve patient satisfaction by paying increasing attention to the physician-patient relationship through strong bedside manner and empathetic communication.